SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY IN TERMS OF GLOBALIZATION: DEFENITION AND BASIC FACTORS - Ключко, В. Г. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The essence of the globalization as socio-political phenomenon is characterized, its negative and positive effects are defined in the work. The work provides the analysis of the approaches to the definition of the essence of the term “national economy” and defines its main purposes and tasks. It considers the basic characteristics of sustainable development, proves the significance of the implementation of the concept of sustainable development exactly at the national level and defines the basic factors of sustainable development of national economy.Key words: globalization, economic growth, econo